Regulatory challenges in Africa an empirical analysis - Mwandosya, Mark. (Dar es Salaam Mkuki na Nyonta, 2021)
Regulation as a tool for pursuing equitable national development and the provision of adequate goods and services is an often enigmatic and inadequately understood subject. In this book, Professor Mark Mwandosya unravels the subject from theory to practice. He explains the rationale for, and objectives of, regulation in several economic sectors and addresses the policy, legal and institutional arrangements and mechanisms normally employed as well as the advantages and pitfalls of alternative approaches. The examples given elucidate these aspects not only on Tanzania and other African countries but also include cases from across the globe. Professor Mwandosya draws on the extensive experience that he has acquired over more than three decades as a senior policy adviser to the Tanzania government; as one of the architects of Tanzania's regulatory reforms; as a government minister who established or oversaw several regulatory authorities in the telecommunications, transport, water, energy and environment sectors; and as an African scholar.
Includes index
Keywords: Regulation